THE ROLE OF DIGITAL LITERACY IN ENHANCING ENGLISH LANGUAGE ACQUISITION AMONG UNIVERSITY STUDENTS - Suyunova Zarina Adham qizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
In the era of rapid technological advancement, digital literacy has become an essential tool in facilitating English language learning. This article explores how university students use digital platforms and online resources to enhance their English proficiency. The study highlights various digital tools such as mobile apps, online dictionaries, educational YouTube channels, and AI-powered language assistants. The article also presents practical recommendations for integrating digital literacy into language education to increase student motivation and autonomy.